P080: Factors predicting morbidity and mortality associated with pre-hospital "lift assist" calls. (2nd June 2016) - Leggatt, L.; Davis, M.; Columbus, M.; Van Aarsen, K.; Lewell, M.; Dukelow, A.
Abstract : Introduction: When an individual requires assistance with mobilization, emergency medical services (EMS) may be called. If treatment is not administered and the patient is not transported to hospital, it is referred to as a "Lift Assist" (LA) call. We have previously shown that LA are associated with morbidity and mortality. What places patients at an increased risk for morbidity and mortality is not yet known.Objective : To determine factors that are associated with increased risk of 14 day morbidity, determined by an ED visit or hospital admission, and mortality in LA calls.Methods: All LA calls from a single EMS agency were collected over a one-year period (Jan - Dec 2013). These calls were linked with hospital records to determine if LA patients had a subsequent visit to the emergency department (ED), admission, or death within 14 days. Logistic regression analyses were run to predict ED visit or hospital admission within 14 days of the LA call from patients' age, gender, co-morbidities and vital signs at the initial LA call.Results: Of 42, 055 EMS calls, 808 (1.9%) were LA calls. There were 169 (20.9%) ED visits, 93 (11.5%) hospital admissions and 9 (1.1%) deaths within 14 days of a LA. Patient age > 61 (p < 0.001) and history of cardiac disease (p = 0.006) significantly predicted ED visit, while patient age >61 (p = 0.001) and an Ambulance Call Record (ACR) missing at least 1 vital sign (p = 0.017) significantly predicted hospital admission. There was a 10% increase in risk of ED visit and hospital admission for every 10 year increase of age after the age of 61. Of the 96 patients with at least 1 missing vital sign, 14 (14.5%) were coded as patient refusals. The sample size was too small to determine predictors for mortality.Conclusion: Patients at risk for morbidity are older than 61 years of age and have co-existing cardiac disease. Patients who are greater than 61 years of age and had at least one missing vital sign on the ACR were more at risk for hospital admission.